Self-esteem as a Pedagogical Condition of Forming Positive Learning Motivation among Primary School Age Children - Valentyna Shyshenko (Pedagogical Discourse, 2011)
The author of the article identified the components of a person self-identity in connection with educational activity in which the teenager is asserting itself. It is indicated that failures cause the adolescent experience, force to reconsider own capabilities, skills, to reduce the level of rigor or to start work on self-improvement. Adequate teenagers’ self-esteem is formed under favorable external conditions: rigor, fairness and friendliness to the teenager in the family, an objective teachers’ evaluation of personality traits and the results of educational activities, adequate social thought.